The Training of Trademark Registration for Usaha Mikro Kecil Menengah (UMKM) to Protect Hak Kekayaan Intelektual (HKI) - Ani Mardiantari; Agus Setiawan; Moh. Dimyati; Ita Dwilestari; Anggita Vela (CV. Creative Tugu Pena, 2022)
The training trademark registration were important to support the development of a business product. Several members of Fatayat NU Batanghari have businesses that produced many products of economic value. The limited knowledge people was about trademarks of products did not have brand. Hence, the purpose of this article was to increase knowledge about trademark registration and the process of registered trademarks at the Direktorat Jendral Kekayaan Intelektual (DJKI). The method used Community Based Research (CBR) with 50 participants of PAC Fatayat NU Group of Bumiharjo Village, Batanghari East Lampung. The collecting data used observation, documentation and conducting Forum Group Discussion (FGD). Furthermore, the result product have a legitimate brand. Hence, it has a high economic value and avoids plagiarism by irresponsible people. This Community Service used the Community Based Research (CBR) method and the sample was 50 participants. The result of this service community showed that the participants could engage their knowledge about the importance of legally registering business product trademarks. Especially Fatayat NU Batanghari group got the rights from the trademark registration of thier business product. Keywords: Training Trademark Registration, Hak Kekayaan Intelektual, Registration of UMKM